Implementation of antinuclear antibodies in autoimmune diagnostic tests: a literature review from immunological aspects - Ni Luh Putu Harta Wedari; Ni Nyoman Sri Budayanti; I Dewa Made Sukrama; I Putu Bayu Mayura (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
Antinuclear antibodies (ANA) test is mainly used in confirming autoimmune disorders such as systemic lupus erythematosus (SLE) and connective tissue diseases e.g., Sjogren’s Syndrome and rheumatoid arthritis. ANA test is often being used as a screening tool for further serological examination. This review aims to explore immunological aspects of anti-nuclear antibodies implementation in autoimmune diagnostic tests. Fluorescent antinuclear antibody (FANA) tests are often being applied since they have high sensitivity and are pretty simple to perform, however, this test has low specificity in diagnosis. In doing this method, patient samples are first diluted then incubated with Hep-2 cells or mouse kidney in glass slides in order to proceed specific binding of antinuclear antibodies. Roughly, around 2% of healthy people and 75% of elderly are positive for FANA test. In contrast, around 5% of people suffering from SLE are negative. Even though it is only seen in 50% up to 70% of SLE patients, ds-DNA antibodies are still the main confirmatory diagnostic gold standard for SLE, particularly in the low amount of C3 complement. Beside ANA, the other diagnostic tests considerably applied are complete blood count test, level of muscle enzyme serum, CXCL4 serum level. Paediatric patients with PM-scleroderma overlapping have been revealed to possess strong positive ANA; anti-Ro/SSA antibody is considered to be the most frequent myositis associated antibody (MAA) in myositis patients.